PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN GROUP INVESTIGATION DAN NUMBERED HEAD TOGETHER PADA MATERI PENCEMARAN LINGKUNGAN DI KELAS VII SMP NEGERI 8 PEMATANGSIANTAR TAHUN PELAJARAN 2019/2020 - Rosenta Purba, Ika (Jurnal Metabio, 2021)
This study aims to determine the differences in student learning outcomes using the Group Investigation and Numbered Heads Together learning models on environmental pollution in seventh-grade students at SMP Negeri 8 Pematangsiantar in the 2019/2020 academic year. The population in this study was all seventh-grade students at SMP Negeri 8 Pematangsiantar in the 2019/2020 academic year, consisting of eight classes with a total of 340 students. The sampling process was carried out using random class or cluster random sampling to obtain two classes: class VII-D as experimental class I using the Group Investigation learning model and class VII A as experimental class II using the Numbered Heads Together learning model. Data analysis was carried out by finding the average value, standard deviation, and hypotheses were tested using statistics or the t-test at a significance level of α = 0.05. The results obtained the average pre-test scores of experimental class I and experimental class II were 44.86 and 40.27, respectively. The post-test scores of experimental class I and experimental class II were 83.78 and 87.03 with a difference of 3.25. From the results of the hypothesis test using the t test, it was obtained that t count (2.517) > t table (1.66629), so Ha was accepted and H0 was rejected, meaning there was a difference in student learning outcomes using the Group Investigation and Numbered Head Together learning models on environmental pollution material for class VII of SMP Negeri 8 Pematangsiantar in the 2019/2020 academic year. It was concluded that there was a difference in student learning outcomes using the Group Investigation and Numbered Head Together learning models on environmental pollution material for class VII of SMP Negeri 8 Pematangsiantar in the 2019/2020 academic year.